Behaviour of cold-formed plain channels under compression - Ananthi, G. Beulah Gnana; Knight, G.M. Samuel; Iyer, Nagesh.R.; Marimuthu, V. (Journal of Structural Engineering, 2024)
This paper presents the results of a parametric study conducted on cold-formed steel plain single channel columns with fixed ends, loaded concentrically and eccentrically. Experimental investigations on columns of slenderness ratios 40 and numerical investigation on columns of slenderness ratio 40, 80,100 and 120 were conducted. Two different cross sections of cold-formed channels CFC 200×50×2 mm and CFC 150×50×2 mm were chosen and forty different analytical studies were performed. The flat width to thickness ratio of all the specimens considered in this study is more than the limiting value. Based on the studies, the effect of slenderness ratio and eccentricity on the load carrying capacity is presented. The Finite Element software ABAQUS was used for numerical studies and the variation in stress contours and the load verses deformation behaviour of columns were studied and compared with the experimental results. Strengths predicted by the North American, the Indian and the British Standards were also compared with the numerical and the experimental results. It was observed that the design strengths predicted by the various standards are generally conservative for both concentrically and eccentrically loaded columns. Specimens with lower slenderness ratio failed by local buckling of the flanges whereas the specimen with higher slenderness ratio of 100 and 120 the failure was by overall flexural buckling. The failure modes predicted by the numerical investigation was similar to the experimental results.